2018
DOI: 10.3389/fcimb.2018.00341
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric Repeat-Binding Factor Homologs in Entamoeba histolytica: New Clues for Telomeric Research

Abstract: Telomeric Repeat Binding Factors (TRFs) are architectural nuclear proteins with critical roles in telomere-length regulation, chromosome end protection and, fusion prevention, DNA damage detection, and senescence regulation. Entamoeba histolytica, the parasite responsible of human amoebiasis, harbors three homologs of human TRFs, based on sequence similarities to their Myb DNA binding domain. These proteins were dubbed EhTRF-like I, II and III. In this work, we revealed that EhTRF-like I and II share similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…This also indicates that TRF2 controls the association of LMNB1 to PCH. This might result from a direct TRF2-LMNB1 interaction that is currently under investigation (Mendez-Bermudez et al, unpublished) and previously suggested for the TRF2 ortholog of the parasite Entamoeba histolytica 34 .…”
Section: Discussionmentioning
confidence: 72%
“…This also indicates that TRF2 controls the association of LMNB1 to PCH. This might result from a direct TRF2-LMNB1 interaction that is currently under investigation (Mendez-Bermudez et al, unpublished) and previously suggested for the TRF2 ortholog of the parasite Entamoeba histolytica 34 .…”
Section: Discussionmentioning
confidence: 72%
“…Lastly, eitrf-like I and II are expressed in specific stages (Figure 5B) in which replication occurs, as nuclear division is necessary for encystment; therefore, these proteins could be required for telomeric protection. TRF-like proteins have been identified and characterized in T. brucei, T. cruzi, L. major, and E. histolytica, where their role as telomere DNA-binding proteins has been reported to provide a possible function in telomere-end protection [24,25,68].…”
Section: Expression Analysis Of the Eimyb Genes During Trophozoite Di...mentioning
confidence: 99%